A BRIEF OVERVIEW OF LUXURY TOURISM IN TURKEY - ŞEN , Burak (SSD Journal, 2024)
Luxury tourism is a travel segment that offers high quality, comfort and exclusive services in travel experiences. This type of travel is often preferred by people seeking opulence, comfort and unique experiences. Luxury tourism is offered in many forms around the world, including private jets, private guided tours, yacht tours and villa hotels with private pools. These trips and activities often offer customized services based on personal preferences, and guests are provided with luxury and comfort throughout their trip. Turkey, with its rich history, natural beauty and diverse cultural offerings, is an attractive destination for luxury tourism and offers a wide range of possibilities. First of all, luxury comfortable resorts offer high quality accommodation, exclusive services and unique experiences in every period. In particular, there are many luxury hotels in Bodrum, Antalya, Istanbul, Cappadocia. Luxury yacht tours in Turkey are also very popular. The Aegean and Mediterranean coasts are an ideal option to go on a blue cruise, stay on a luxury yacht and look at the coastal cities. These tours offer personalized services, gourmet meals and spectacular views. Turkey is also a destination that offers luxury gastronomic experiences. Istanbul's world-renowned restaurants offer rich and regional flavors of Turkish cuisine. Cultural experiences also play an important role in luxury tourism. Turkey's historical and cultural richness offers a unique experience to luxury. For example, Cappadocia offers experiences such as hot air balloon tours, historical data, private guided tours and special events in Ottoman palaces. In conclusion, Turkey is a destination that offers many opportunities for luxury tourism. There are a variety of options such as luxury properties, luxury yacht tours, gastronomic experiences and cultural activities. Turkey's rich history and natural beauty offer a luxurious and spectacular experience.